Dual inhibitors of DNMT and HDAC induce viral mimicry to induce antitumour immunity in breast cancer - Wenjun Huang; Qingyun Zhu; Zhichao Shi; Yao Tu; Qinyuan Li; Wenwen Zheng; Zigao Yuan; Lulu Li; Xuyu Zu; Yue Hao; Bizhu Chu; Yuyang Jiang (Cell Death Discovery, 2024)
Abstract The existing conventional treatments for breast cancer, including immune checkpoint blockade, exhibit limited effects in some cancers, particularly triple-negative breast cancer. Epigenetic alterations, specifically DNMT and HDAC alterations, are implicated in breast cancer pathogenesis. We demonstrated that DNMTs and HDACs are overexpressed and positively correlated in breast cancer. The combination of DNMT and HDAC inhibitors has shown synergistic antitumour effects, and our previously designed dual DNMT and HDAC inhibitor (termed DNMT/HDACi) 15a potently inhibits breast cancer cell proliferation, migration, and invasion and induces apoptosis in vitro and in vivo. Mechanistically, 15a induces a viral mimicry response by promoting the expression of endogenous retroviral elements in breast cancer cells, thus increasing the intracellular level of double-stranded RNA to activate the RIG-I–MAVS pathway. This in turn promotes the production of interferons and chemokines and augments the expression of interferon-stimulated genes and PD-L1. The combination of 15a and an anti-PD-L1 antibody had an additive effect in vivo. These findings indicate that this DNMT/HDACi has immunomodulatory functions and enhances the effectiveness of immune checkpoint blockade therapy. A novel dual DNMT and HDAC inhibitor induces viral mimicry, which induces the accumulation of dsRNA to activate tumoral IFN signalling and cytokine production to enhance the immune response in breast cancer.